Diversidade beta da assembleia de epífitas entre árvores em pastagens e fragmentos de Mata Atlântica - Silva, Bianca Aparecida Borges E (2023)
Beta diversity can be understood as a measure that compares diversity on two different scales: alpha and gamma. The transformation from land use to pastures and intensive agriculture creates agricultural mosaics in landscapes where fragments of various crops and pastures connect with natural areas, imposing spatially uniform conditions on the landscape, causing loss of habitat, refuge, food and corridors of dispersal, conditions that are tolerable only by a small subset of abundant native species, causing local beta diversity to decrease. Epiphytes are particularly sensitive to forest fragmentation, due to their very specific ecological habits, as they are atmospheric plants and live without connection to the soil, depending directly on their phorophytes. The aim of this study was to answer whether: (1) Is the pattern of additive partitioning of diversity between epiphyte assemblages in grassland and forests similar? (2) Does the formation pattern of epiphyte assemblages result from species replacement or nesting processes? and (3) Are these processes different between pastures and forests? For this, we used data on the richness and abundance of epiphytic Angiosperms collected in 15 landscapes, each consisting of a forest fragment with an adjacent pasture. We sampled epiphytes on 600 trees in the forests and 720 in the pastures. We calculated the beta diversity through the additive diversity partition. We found a total of 10,298 individuals belonging to 23 species and four families: Bromeliaceae, Orchidaceae, Cactaceae and Piperaceae. In the pastures we found 9939 individuals, belonging to 16 species. Bromeliaceae was the family found with greater abundance, mainly three Tillandsia species, and Orchidaceae with greater richness. In the forests we found 359 individuals, belonging to 18 species. Orchidaceae was the richest and most abundant family. We verified that despite the difference in richness being low, the beta diversity between forests and pastures was high, due to the change in dominance of some species in the pastures, mainly the overpopulation of the genus Tillandsia (Bromeliaceae), and the main responsible process was the nesting. We conclude that the remaining forest fragments are not in a good state of conservation, but still support a community of vascular epiphytes adapted to these environments, which play a very important role in the ecosystem.